2018
DOI: 10.1128/iai.00552-17
|View full text |Cite
|
Sign up to set email alerts
|

cas9 Enhances Bacterial Virulence by Repressing the regR Transcriptional Regulator in Streptococcus agalactiae

Abstract: Clustered regularly interspaced palindromic repeats (CRISPR) and their associated genes have been demonstrated to regulate self-genes and virulence in many pathogens. In this study, we found that inactivation of caused reduced adhesion and intracellular survival of the piscine strain GD201008-001 and significantly decreased the virulence of this strain in zebrafish and mice. Further investigation indicated that the transcriptional regulator was upregulated in the Δ mutant. As mediates the repression of hyaluro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 56 publications
3
39
0
Order By: Relevance
“…Recently, it has been reported that CRISPR-Cas systems may also play a regulatory role on endogenous genes. Thus, in addition to protecting from phages, these systems are increasingly being recognized as regulators of bacterial virulence ( Louwen et al, 2014 ; Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that CRISPR-Cas systems may also play a regulatory role on endogenous genes. Thus, in addition to protecting from phages, these systems are increasingly being recognized as regulators of bacterial virulence ( Louwen et al, 2014 ; Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Type II CRISPR interference, CRISPR-associated protein 9 (Cas9), an RNA-guided DNA endonuclease, complexes with a trans- activating small RNA (tracrRNA) and small guide CRISPR RNAs (crRNA, derived from the CRISPR array), and this ribonucleoprotein complex targets foreign invading DNA for degradation (Marraffini and Sontheimer, 2010). Recently, Cas9 has been associated with bacterial virulence, immune evasion, and interaction of pathogens with host cells via endogenous regulation of gene expression (Sampson and Weiss, 2013a, b; Dugar et al, 2018; Ma et al, 2018). However, the Cas9 regulon and the mechanism by which Cas9 regulates gene expression has only begun to be elucidated and varies between bacteria; therefore, further study into the conservation of the Cas9 regulon and regulatory mechanism across other cas9- encoding pathogens, such as GBS, is needed.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Cas9 regulon and the mechanism by which Cas9 regulates gene expression has only begun to be elucidated and varies between bacteria; therefore, further study into the conservation of the Cas9 regulon and regulatory mechanism across other cas9- encoding pathogens, such as GBS, is needed. A previous study on a GBS strain isolated from tilapia indicated that Cas9 influenced virulence (Ma et al, 2018); however, the role of Cas9 in both GBS colonization and disease in clinically relevant human isolates, such as those of ST-17 lineage, has not been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that intrinsic control does not require dedicated transcription factors and may be a more general property of CRISPR-Cas biology. It remains to be seen whether other CRISPR-Cas types have evolved their own RNA-guided intrinsic regulators, for instance using degenerate self-targeting spacers 60 .…”
Section: Discussionmentioning
confidence: 99%